PENGARUH KUALITAS PELAYANAN JKBM TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD KLUNGKUNG TAHUN 2014 - Rolan, Ade; Pascarani, Ni Nyoman Dewi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRACT The focus of this research is the Effect of JKBM Service Quality on Inpatients Satisfaction at Public Hospital of Klungkung Regency Year 2014 by using problemâ€™s formulation â€œhow great the Effect of JKBM Service Quality on Inpatients Satisfaction at Public Hospital of Klungkung Regency?â€. The method used in this research was associative quantitative because the objective of this research was to know the effect and the relation between two variables. The research population was 138 on Inpatients that use JKBM service at Public Hospital of Klungkung Regency, with the sample amount was 103 respondents. Indicators used to measure the Quality of JKBM Service in this study gained from Lenvinne theory (1990) that contains 3 indicators are Responsiveness, Responsibility, and Accountability, four factors that be able to influence customers satisfaction according to Rangkuti (2006) that consists of Value, Competitiveness, Customers Perception, Service Stages, and Service Moment. The collecting data used questionnaires. The data analysis technical used simple linear regression test resulted Y = 4,115 + 0,388 X1, means that high and low quality of JKBM service gained by inpatients Satisfaction of Public Hospital at Klungkung Regency. Simple correlation analyzed result (R) was 0.866, positive or unidirectional, t-test test with accounting result of tcount was greater than ttable (17.417> 1.658), so HO refused and H1 accepted. So it can be concluded there is significant Effect between JKBM Service Quality towards inpatients Satisfaction at Public Hospital of Klungkung Regency Year 2014 with the amount 75% while the restâ€™s amount 25% influenced by other factors. So the researcherâ€™s hypothesis stated that "there is Effect between JKBM Service Quality Towards Inpatients Satisfaction at Public Hospital of Klungkung Regency Year 2014 based on the researchâ€™s result or it can be said to be accepted. Keywords : Service Quality JKBM, Inpatients Satisfaction.